Laparoscopic Free Omental Lymphatic Flap for the Treatment of Lymphedema. Issue 1 (July 2015) - Nguyen, Alexander T.; Suami, Hiroo
<x xml:space="preserve">Abstract</x> Summary: Advances in microsurgery have displayed promising results for the treatment of lymphedema. The use of vascularized lymph node transfers has increased in popularity but incurs the potential risk for donor-site lymphedema. The omentum has been previously described for the treatment of lymphedema but has been overlooked because of presumed high morbidity, including the need for celiotomy and pedicled complications. The authors present a novel technique and early results of the laparoscopic free omental lymphatic flap for the management of lymphedema. The minimally invasive harvest successfully avoids both the previously associated morbidity of this flap and the risk of iatrogenic lymphedema to the donor site. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, V.